Uma proposta de uso de programação em blocos para desenvolvimento de jogos físicos e incentivo a área STEM - Assis, Ricardo Henrique da Silva (Universidade Federal de São Carlos, 2025)
The present work addresses the urgent need to attract talent to STEM fields (Science, Technology, Engineering, and Mathematics), recognizing the importance of these áreas for technological advancement and innovation. One tool that can play a significant role in this process is BIPES—a platform that uses block-based programming to simplify the development of embedded systems projects. Acknowledging the strong appeal of games for elementary and high school students, this study proposes an innovative approach that leverages BIPES to assist students in building physical game prototypes. These projects integrate components such as buttons, potentiometers, and displays. To this end, the project developed and implemented playful programming blocks, code snippets, and instructional guides that support students in constructing physical games through block-based programming and the assembly of prototypes using low-cost, easily accessible electronic components. It was possible to build (and test) step-by-step guides for assembling physical game devices and programming them to implement a version of the classic PONG game and a Space Invaders-style game. This outcome—centered around the theme of gaming—proves to be highly motivating for students at various levels and aims to foster the development of new talent while supporting continued progress in STEM education.
A proposal for the use of block-based programming for the xevelopment of physical games and the promotion of STEM education
Keywords: BIPES; MicroPython; STEM; Jogos; Construcionismo; Educação; Games; Constructionism; Education; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO